Socio-economic conditions of refugees’ settlement in Bulgaria in the 1920s - Paszkiewicz, Jędrzej (Balcanica Posnaniensia. Acta et studia, 2018)
The influx of immigrants into Bulgaria during the first two decades of 20th century was aresult of the two lost armed conflicts and border shifts between 1913 and 1918. These changesin turn resulted in disruption of the socio-political and economic situation within the country.The government was unable to efficiently overcome the consequences of high immigration,which aggravated the already present social and economic difficulties and threatened the internal stability of the state. On the other hand, in spite of the grave political and economiccrisis, certain measures were undertaken to counter the negative tendencies, with state supportfor the agricultural settlement. The partial success of the above was possible due to theagriculture reform introduced in 1924 and financial credits from abroad (1926, 1928). Theoutcome was sufficient for the Bulgarian government to deem the settlement action a success, an enhancement of the country's internal stability and appeasement of the general public. Nevertheless, a number of pressing issues remained, resulting mostly from a lack of systemic support to the immigrants and their families. The refugee integration process was hindered bythe lack of a secure economic foundation and the differences among the particular socialgroups.